2015
DOI: 10.1097/brs.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology and Clinical Significance of the Extraforaminal Ligaments at the Cervical Level

Abstract: Between the cervical spinal nerves and nearby structures, there are 2 types of the EFLs. The radiating ligaments may serve as a protective mechanism against traction and play an important role in the positioning of the nerves in the intervertebral foramen. However, in all probability, the transforaminal ligaments may be the underlying cause of the cervical radiculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…Both of these structures are protected against pulling out (avulsion) by fibrous attachments binding the spinal nerves to the transverse processes and the ganglia to the IVFs. 2,4,5,8,9,12,15,[18][19][20][21]26,27 The IVF in the subaxial cervical spine is limited by the following: 1) the inferior part of the superjacent vertebral body, the uncovertebral joint, and the posterolateral part of the anulus fibrosus anteriorly; 2) adjacent pedicles inferiorly and superiorly; and 3) the medial aspect of the facet joint posteriorly. Outside the foramina arise the transverse processes directed laterally and forward; each consists of an anterior and a posterior part.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of these structures are protected against pulling out (avulsion) by fibrous attachments binding the spinal nerves to the transverse processes and the ganglia to the IVFs. 2,4,5,8,9,12,15,[18][19][20][21]26,27 The IVF in the subaxial cervical spine is limited by the following: 1) the inferior part of the superjacent vertebral body, the uncovertebral joint, and the posterolateral part of the anulus fibrosus anteriorly; 2) adjacent pedicles inferiorly and superiorly; and 3) the medial aspect of the facet joint posteriorly. Outside the foramina arise the transverse processes directed laterally and forward; each consists of an anterior and a posterior part.…”
Section: Discussionmentioning
confidence: 99%
“…18,31 The attachments of the BP roots to the spine have been investigated in order to elucidate the mechanism of traction injuries. 9,15,21,26,27,31 In 1951 Frykholm observed that the epineurium of the cervical spinal nerve and ganglion is firmly anchored in the groove of the underlying transverse process. Moreover, the ligaments descending from the transverse processes of C4-6 reinforce the epineurial sheaths of the trunks lying below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ventral and dorsal extraforaminal ligaments also consist of a superior and inferior part. The inferior ventral and dorsal ligaments are attached to each other [28,43].…”
Section: Extraforaminal Ligaments Of the Cervical Spinal Nervesmentioning
confidence: 99%
“…The posterior side of the transforaminal ligaments is strongly adherent to the spinal nerve sheath. Usually, an intervertebral foramen contains no more than one transforaminal ligament [43].…”
Section: Extraforaminal Ligaments Of the Cervical Spinal Nervesmentioning
confidence: 99%